PERLINDUNGAN HUKUM PADA ANAK YANG MENJADI KORBAN KEKERASAN SEXSUAL DILINGKUP KELUARGA - Sampurno, Heri (Jurnal HUKUM BISNIS, 2025)
Nowadays there are many victims of violence experienced by children, so the author wants to discuss legal assistance for children who are victims of criminal acts of sexual violence in the family environment. To analyze the extent of legal assistance to children who are victims of criminal acts of sexual violence in the family environment. This research uses normative legal research methods. By using normative legal research methods, researchers focus on studying the application of norms or rules in positive law which are then linked to with the problems that are the main subject of this research. Protection for victims of sexual crimes, namely the existence of prevention efforts or efforts to overcome them after the crime occurs, protection in these legal efforts. By providing supervision/protection from various threats that would endanger victims. Then there is providing adequate medical assistance. A form of legal protection for children who are victims of sexual violence by getting treatment and opportunities in accordance with their needs in various areas of life, so that in providing legal protection for children by the government it must be based on the Principles of Children's Rights, namely respect, and protection of children's rights.